Recent developments in the field of cachexia, sarcopenia, and muscle wasting: highlights from the 11th Cachexia Conference. Issue 1 (28th March 2019) - Ebner, Nicole; Anker, Stefan D.; von Haehling, Stephan
Abstract: This article highlights the updates from preclinical and clinical studies into the field of wasting disorders that were presented at the 11th Cachexia Conference held in Maastricht, the Netherlands, in December 2018. Herein, we summarize the biological and clinical significance of different markers and new diagnostic tools and cut‐offs for the detection of skeletal muscle wasting, including micro‐RNAs, siRNAs, epigenetic targets, the ubiquitin–proteasome system, mammalian target of rapamycin signalling, news in body composition analysis including the D3‐creatine dilution method, and electrocardiography that was modified to enable segmental impedance spectroscopy. Of particular interest were the beneficial effects of BIO101 on muscle cell differentiation, hypertrophy of myofibers associated with mammalian target of rapamycin pathways activation, and the effect of metal ion transporter ZIP14 loss that reduces cancer‐induced cachexia. The potential of anti‐ZIP14 antibodies and zinc chelation as anti‐cachexia therapy should be tested in patients with cancer cachexia. Big randomized studies were presented such as RePOWER (observational study of patients with primary mitochondrial myopathy), STRAMBO (influence of physical performance assessed as score and clinical testing), MMPOWER (treatment of elamipretide in subjects with primary mitochondrial myopathy), FORCE (examined differences in relative dose intensity and moderate and severe chemotherapy‐associated toxicities between a strength training intervention and a control group), and SPRINTT (effectiveness of exercise training in healthy aging). Effective treatments were urothelin A, rapamycin analogue treatment, epigenetic factor BRD 4 and epigenetic protein BET, and the gut pathobiont Klebsiella oxytoca . Clinical studies that investigated novel approaches, including urolithin A, the role of gut microbiota, metal ion transporter ZIP14, lysophosphatidylcholine and lysophosphatidylethanolamine, and BIO101, were described. It remains a fact, however, that effective treatments of cachexia and wasting disorders are urgently needed in order to improve patients' quality of life and their survival.